Digital Learning and Its Implementation - Biqi Asshafah Zain (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
Digital learning has become an essential part of modern education along with the development of information and communication technology. This study aims to examine the implementation of digital learning in schools. This study employed a library method, reviewing various relevant literature on digital learning and its implementation to understand concepts, strategies, challenges, and opportunities in modern education. Data was collected through document review and then systematically analyzed using content analysis to identify themes and patterns related to the topic. Digital learning has been shown to increase student motivation, participation, and creativity through interactive media and visual materials, as well as support the development of 21st-century skills such as critical thinking and collaboration through project-based learning models. However, the success of this method depends heavily on the teacher's pedagogical approach, which is able to design meaningful and relevant learning and act as a facilitator and motivator in creating an effective digital learning ecosystem.